Addition Effect of Petrasoil Additive Material on CBR Value of Soil in Swamp Areas - Andi Herius; Indrayani Indrayani Indrayani; Arfan Hasan; Ahmad Mirza (Research Centre of Inorganic Materials and Complexs, 2019)
Some road construction projects use petrasoil additive to increase soil stabilization, one of then is the Improvement of Tabarfane-Hokmar (Chemical Petrasoil) Road Project in Aru Selatan Timur District, Aru Islands. To obtain the influence of petrasoil aditive material as soil stabilization in swamp areas, a research is needed. petrasoil additives that powder shape are dissolved in water with 3 variations, namely 500 liters, 750 liters, and 1000 liters of water. Tests which carried out include compaction testing, index properties, and CBR. The results showed that the addition of petrasoil mixture with water without being combined with other added ingredients could lead to increasingly unstable soil conditions where the soil water content increased and the dry weight of the soil diminished, meaning that soil density decreases, and the CBR value of soil decreases.